Method for recycling PET-titanium aluminum nitride composite material cutting chippings

By separating PET-titanium aluminum nitride composite materials through steps such as low-temperature freezing, ball milling, and calcination, the problem of insufficient recycling and treatment is solved, achieving efficient and clean resource separation and purification, which is suitable for industrial applications.

CN121314993APending Publication Date: 2026-01-13LUOYANG XINHAI ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511718278.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-21
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

In the current technology, the recycling and treatment of cutting debris from PET-titanium nitride aluminum composite materials is insufficient, resulting in low resource utilization and environmental pollution and safety risks.

Method used

PET and titanium aluminum nitride are separated by low-temperature freezing and ball milling. Then, valuable components such as titanium, aluminum and manganese are separated and purified by selective dissolution and precipitation reactions through steps such as calcination, leaching, acid washing and water washing.

Benefits of technology

It achieves efficient and clean separation and recovery of high-value components in PET-titanium aluminum nitride composite materials, improves resource utilization, simplifies process flow, reduces equipment investment and safety risks, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121314993A_ABST
    Figure CN121314993A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recycling PET-titanium aluminum nitride composite material cutting chips, and belongs to the technical field of solid waste resource recycling. The method sequentially comprises the steps of scrap pretreatment, separation of an organic component PET, high-temperature roasting, acid leaching, precipitation and purification of a titanium component, precipitation and purification of an aluminum component and the like. Through a set of integrated technological process, efficient separation of organic components and inorganic components in the composite material is achieved, and high-value titanium and aluminum elements are subjected to multi-section directional conversion to be prepared into high-purity titanium dioxide and aluminum hydroxide products respectively.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of solid waste resource recycling, and particularly relates to a method for recycling PET-titanium aluminum nitride composite material cutting chips. BACKGROUND

[0002] With the progress of science and technology, various new materials gradually move from the laboratory to various application fields, and play an increasingly important role in national defense, communication, energy and other fields. PET-titanium aluminum nitride composite material is a very representative new material, which is widely used in: 1) electronic device mold, high-performance waterproof and breathable film in the communication industry; 2) super capacitor, lithium ion battery in the energy industry; 3) flexible transparent electrode, electromagnetic interference shielding, static dissipation material in the electronic industry; 4) solar seawater desalination membrane in the field of seawater desalination; 5) high-performance barrier and electronic shielding material in the packaging industry. PET-titanium aluminum nitride composite material will generate a large amount of cutting chips during processing. These chips are a complex mixture of PET macromolecules and high-value titanium aluminum nitride ceramic phases. At present, there is a lack of effective and economic recycling technology for such composite waste in the industry. The mainstream treatment method is still landfill or incineration as ordinary industrial solid waste. This traditional treatment method has serious waste of resources and potential environmental pollution.

[0003] There is little research on the recovery and treatment method of titanium nitride or aluminum nitride in the prior art. The patent with publication number CN1069072A discloses a method for recovering titanium from a composite substrate containing titanium nitride, which includes the following two steps: (1) titanium nitride is prepared from titanium slag; (2) titanium tetrachloride is prepared by reacting the prepared titanium nitride with chlorine. However, the patent has the following problems: (1) In the laboratory or industrial device implementing the method, a collection device with cooling, constant temperature holding and temperature display functions must be provided at the outlet section of the reactor. This system is crucial, and its purpose is to ensure that the gaseous reaction product (titanium tetrachloride vapor) can be safely and controllably cooled and liquefied (or sublimed) and collected. The above-mentioned key collection facilities are not described in the technical description of the existing patent, which reflects the shortcomings in the design of the process integrity, and there is a safety risk and affects the effective recovery rate of the product; (2) The scheme does not set up a tail gas treatment unit, and does not treat the excess chlorine or harmful gases produced by the side reaction, which causes environmental pollution and health problems. At the same time, the scheme lacks a blowback facility. Since titanium tetrachloride is prone to hydrolysis reaction with moisture in the air, if there is no effective anti-backflow measure (such as a one-way valve, a sealed liquid seal, etc.), air will enter the system, causing the product to hydrolyze and deteriorate. The final product will be a mixture of titanium tetrachloride and titanium dioxide, not pure target product, thus causing the failure of the entire process.

[0004] Therefore, developing a method capable of efficiently and cleanly recycling PET-titanium aluminum nitride composite cutting chips and realizing the separation and high-value reuse of valuable components (especially titanium and aluminum resources) therein has become a technical problem urgently to be solved in the field. This not only has significant economic benefits, but also has important strategic significance for promoting the green and closed-loop development of the new material industry. SUMMARY

[0005] In view of the technical problems of insufficient recycling of PET-titanium aluminum nitride composite materials and low resource utilization, the present application provides a method for recycling PET-titanium aluminum nitride composite cutting chips, which efficiently separates high-value components in waste materials.

[0006] In order to achieve the above-mentioned purpose, the technical scheme of the present application is as follows: The present application provides a method for recycling PET-titanium aluminum nitride composite cutting chips, and the specific steps are as follows: (1) Separation of PET: The cutting chips are frozen at low temperature, then sent to ball milling, mainly to separate the PET and titanium aluminum nitride on each chip; after repeated 3-6 times of low temperature freezing and ball milling, the PET is separated by cyclone separation and gravity flotation, using the density difference to separate the PET, to obtain PET powder and titanium aluminum nitride residue; this step utilizes the brittle nature of PET material after repeated freezing, and the PET and titanium aluminum nitride can be easily separated after ball milling after each freezing. Ultrasonic defoaming is used in flotation, and ultrasonic cavitation effect is used to remove bubbles in water, especially small bubbles wrapped in the chips, which will affect the flotation effect and cause titanium aluminum nitride chips to also float on the water surface.

[0007] (2) Roasting: the titanium aluminum nitride residue obtained in step (1) is mixed with sodium carbonate, liquid alkali, sodium chloride and manganese dioxide to form balls, and then sent into an atmosphere furnace for roasting. Before roasting, nitrogen is introduced to remove air, and then the temperature is raised in stages. First, the temperature is raised to 300-320°C, and the temperature is maintained for 0.5-2h. Then, when the temperature is raised to 500°C, air is introduced. Then, the temperature is raised to 750-1000°C, and the temperature is maintained for 1-4h. During the roasting process, the pressure in the roasting furnace is maintained at normal pressure, and a gas preheating device is arranged at the front end of the furnace. In this step, under the condition of high temperature roasting, after the temperature is raised to the target temperature in the first stage, sodium hydroxide forms a molten state and uniformly covers the surface of titanium aluminum nitride. When the temperature is raised to 300-320°C, which is the melting point of sodium hydroxide, an alkali corrosion effect is generated, which corrodes and disintegrates the debris into fine particles, facilitating subsequent reactions. Before 500°C, a nitrogen atmosphere is maintained. Since the reaction of manganese dioxide with sodium hydroxide and sodium carbonate requires oxygen, and manganese dioxide hardly produces oxygen below 500°C, the nitrogen atmosphere can avoid the reaction of manganese dioxide with the two alkalis, causing loss. When the temperature continues to rise, sodium carbonate gradually participates in the reaction and decomposes to generate carbon dioxide gas, and at the same time, manganese dioxide releases oxygen, avoiding the coverage of the material layer by carbon dioxide gas for a long time. At the same time, a large amount of hot air is continuously introduced into the furnace to carry away the newly generated carbon dioxide and nitrogen, so that the oxidation and sodiumization reactions of titanium aluminum nitride continue. The main reaction equations are as follows (note: TiAlN is used to represent titanium aluminum nitride, and the atomic ratio in the chemical formula does not represent the actual ratio): 4TiAlN+6Na2CO3+7O2=4NaAlO2+4Na2TiO3+6CO2+2N2↑(main reaction) 4MnO2=2Mn2O3+O2↑(main reaction, manganese dioxide decomposes under heat) 4TiAlN+12NaOH+7O2=4NaAlO2+4Na2TiO3+6H2O↑+2N2↑(side reaction, titanium aluminum nitride reacts with sodium hydroxide)

[0008] Al2O3+2NaOH=2NaAlO2+H2O (side reaction, a small amount of aluminum oxide film on the surface of the debris reacts with the alkali) Al2O3+ Na2CO3=2NaAlO2+CO2↑ (side reaction, a small amount of aluminum oxide film on the surface of the debris reacts with the alkali) 2Mn2O3+4Na2CO3+O2=4Na2MnO4+4CO2 (side reaction, occurs at 500°C and above) (3) Leaching: the calcined sand obtained in step (2) is ground and stirred with water, and the pH is kept not less than 14 during the process, and then heated leaching; this step utilizes the characteristics that sodium metaaluminate and sodium manganate are dissolved in water under high pH environment, and sodium metatitanate is insoluble in water to separate. The leaching should be heated, and cannot be leached at room temperature, because the structure of sodium metatitanate is strip structure under heating environment, and will curl to form tubular structure when cold, which will wrap a large amount of impurities in the tubular structure, and is not conducive to the purity of the product.

[0009] (4) Titanium extraction: after the leaching is completed, the obtained slurry is filtered by using a filter with heat preservation function to obtain sodium metatitanate filter cake, at this time the product is mainly sodium metatitanate, and also contains other forms of sodium titanate substances; the sodium metatitanate filter cake is sufficiently pickled and filtered to obtain filtrate I, and the obtained filter cake is sufficiently washed with water and then calcined to obtain titanium dioxide; the pickling and washing filtrate in this process can be reused after adding acid and water without affecting the quality of the product, and can be discharged into the sewage treatment system after being reused for a certain number of times. The main reaction equation is as follows: Na2TiO3+H2SO4=Na2SO4+TiO2·H2O (sodium metatitanate is pickled to form hydrated titanium dioxide) TiO2·H2O =TiO2+H2O↑ (hydrated titanium dioxide loses water to form titanium dioxide under heating) (5) Aluminum extraction: the filtrate I obtained in step (4) is added dropwise with concentrated sulfuric acid to adjust the pH to 7-8, and then stirred and filtered to obtain filtrate II, and the filter cake is washed with water to obtain aluminum hydroxide; this step utilizes the hydrolysis and precipitation of Al 3+ , and the pH should not be less than 7 when adjusting the pH to prevent manganese dioxide from being mixed into aluminum hydroxide, and the aluminum element is slightly lost, which is about 3% by detection. The main reaction equation is as follows: Al 3+ +3OH - =Al(OH)3↓ (trivalent aluminum hydrolyzes to form a precipitate) (6) Manganese extraction: the filtrate II obtained in step (5) is added dropwise with concentrated sulfuric acid to adjust the pH to 1-2, and then stirred and filtered, and the obtained filter cake is washed and dried to obtain manganese dioxide, which can be returned to step (2) for recycling. This step utilizes the fact that manganate ions can form complete precipitation under acidic environment with pH<3, and aluminum ions continue to remain in dissolved state, and about 1 / 3 of manganese elements can be returned to step (2) for use. The remaining sewage in the reaction can be discharged into the sewage treatment system. The main reaction equation is as follows: 3MnO4 2- +4H + =MnO2↓+2MnO4 - +2H2O (manganate ions are disproportionated to form manganese dioxide and permanganate ions) The temperature of the low-temperature freezing in the step (1) is -100℃ to -50℃, the time is 0.5 to 2 hours, and the ball milling time is 0.1 to 0.5 hours; the gravity floatation is that water is added according to the liquid-solid ratio of 20:1 mL / g, and then stirred uniformly, and then heated at the power density of 0.5 to 1 W / cm 2 Then, ultrasonic 3 to 5 minutes, and then stirred 3 to 5 minutes, and the above steps are alternately performed 5 to 10 times.

[0010] The liquid alkali in the step (2) is a sodium hydroxide solution with the mass percentage of 30%, and the mass ratio of the titanium aluminum nitride residue to sodium carbonate, liquid alkali, sodium chloride and manganese dioxide is 1:(3-5):(0.05-0.1):(0.1-0.2):(0.01-0.05).

[0011] The liquid-solid ratio of water and calcine in the step (3) is 5-10:1 mL / g, and the heating temperature is 80-100℃, and the holding time is 0.5-2h.

[0012] The pickling solution in the step (4) is a sulfuric acid solution, and the final concentration is 0.1-1 mol / L, the liquid-solid ratio of the sulfuric acid solution to the sodium metatitanate filter cake is 3-5:1 mL / g, and the pickling time is 5-10h; the roasting temperature is 600-1000℃, and the time is 1-3h.

[0013] The present application has the following beneficial effects: 1. The present application innovatively adopts a production process, that is, each valuable component in the PET-titanium aluminum nitride composite scrap can be effectively separated and purified. The method enables the high-value components in the composite material to be classified and extracted, and recycled in a targeted manner, and re-enters the production cycle as high-quality raw materials, greatly improving the resource utilization rate and realizing the transformation from "waste" to "fine raw materials". Each product obtained by the present application has high purity and good physical and chemical properties, and can be directly applied to the downstream industry as high-quality chemical raw materials.

[0014] 2. The process designed by the present application is short and efficient, and does not need complex and long multiple independent systems. By accurately controlling the key steps (such as selective dissolution, precipitation, separation, etc.), the effective deconstruction of the complex system is realized. The process involved in the present application not only reduces the equipment investment cost, but also reduces the operation steps, so that the whole process is more easy to realize the industrialized scale production and stable control. In the recycling process, the present application does not use toxic and harmful hazardous substances, but mainly uses mild acid and alkali solutions or water-based systems. From the source, the safety risks such as fire, explosion and poisoning caused by the use of dangerous chemicals are eliminated, which meets the basic requirements of green chemical industry and safety production, and has excellent environmental benefits. BRIEF DESCRIPTION OF DRAWINGS

[0015] In order to make the technical solutions in the embodiments of the present application or the prior art clearer, the accompanying drawings needed in the embodiments or prior art description will be briefly introduced. Obviously, the accompanying drawings in the following description only represent some of the embodiments of the present application, and all other embodiments obtained by a person of ordinary skill in the art without creative effort based on these drawings also belong to the protection scope of the present application.

[0016] Figure 1 The process flow chart of the PET-titanium aluminum nitride composite material recycling treatment of the present application. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present application will be described clearly and completely in the following with reference to the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments only represent some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative effort also belong to the protection scope of the present application.

[0018] The test methods used in the following experimental examples are conventional methods unless otherwise specified; the materials, reagents, etc. used are reagents and materials available from commercial channels unless otherwise specified.

[0019] The PET content of the material used in the embodiments of the present application is about 50wt%, and the remaining 50% is titanium aluminum nitride material, in which Ti accounts for 63.77%, Al accounts for 35.86%, and N accounts for 0.37wt% (since oxygen is an external element, it is not included in the statistics).

[0020] Example 1 A method for recycling PET-titanium aluminum nitride composite material cutting debris, the specific steps are as follows: (1) Separate PET: take 1000g of cutting debris, freeze at -100℃ for 0.5h, then send to ball milling, repeat the above freezing and ball milling steps for 3 times; then add 1000g of ball milled material into 20L water and stir uniformly, under the power density of 0.5W / cm 2 After 3min of ultrasonic, mechanically stir for 5min, repeat 7 times alternately, then stand still, extract the surface liquid and filter, the filter cake is the recycled PET material; take the lower liquid and filter, the filter cake is the titanium aluminum nitride residue.

[0021] (2) Roasting: 714 g of titanium aluminum nitride residue obtained in step (1) is mixed with 2500 g of sodium carbonate powder, 40 g of liquid alkali, 75 g of sodium chloride powder, and 15 g of manganese dioxide powder; after mixing and balling, it is sent to an atmosphere roasting furnace. Nitrogen is introduced before roasting to remove air. The temperature is first raised to 310°C and maintained for 1.5 hours. When the temperature reaches 500°C, air is introduced. Finally, the temperature is raised to 1000°C and maintained for 1 hour. The roasting furnace maintains a constant pressure, and a gas preheating device is installed at the front end of the furnace.

[0022] (3) Leaching: 1675 g of calcined sand obtained in step (2) is ground to 200 mesh and added to 10050 mL of water for stirring and leaching (liquid-solid ratio 6:1). The pH value is monitored in real time during the process, and the pH value is kept above 14. If it decreases, a small amount of sodium hydroxide powder can be added to adjust it. The leaching temperature is 100°C, and the temperature is maintained for 1 hour.

[0023] (4) Titanium extraction: The leaching slurry obtained in step (3) is filtered while hot. The filtering equipment needs to be maintained at 100°C. 1347 g of sodium metatitanate filter cake obtained by filtration is added to 3292 mL of water and 188.6 g of 98% sulfuric acid to prepare a 0.5 mol / L sulfuric acid solution. Stir thoroughly for 9 hours. After acid washing, filter the cake and wash it thoroughly with water. Roast at 1000°C for 1 hour to obtain titanium dioxide.

[0024] (5) Aluminum extraction: Add concentrated sulfuric acid to the filtrate obtained after acid washing in step (4) to adjust the pH to 8. After thorough stirring, filter the cake. The obtained filter cake is thoroughly washed with water and naturally dried to obtain aluminum hydroxide.

[0025] (6) Manganese extraction: Add concentrated sulfuric acid to the filtrate obtained after filtration in step (5) to adjust the pH to 1. After thorough stirring, filter the cake. The obtained filter cake is thoroughly washed with water and dried to obtain manganese dioxide. The obtained manganese dioxide can be returned to step (2) for continuous use.

[0026] (7) Detection: Element extraction rate and product purity.

[0027] Example 2 A method for recycling PET-titanium aluminum nitride composite cutting debris, the specific steps are as follows: (1) Separate PET: Take 1500 g of cutting debris and freeze it at -80°C for 1.5 hours. After freezing, send it to ball mill grinding. Repeat the previous freezing and ball milling steps 5 times. Then add 1500 g of ball milled material to 30 L of water and stir evenly. The power density is 0.8 W / cm 2After 4 min of ultrasonic treatment, mechanical stirring was performed for 4 min, and this process was repeated 5 times. After standing, the surface liquid was extracted and filtered, and the filter cake was a recovered PET material. The lower layer liquid was filtered, and the filter cake was a titanium aluminum nitride residue.

[0028] (2) Roasting: 1071 g of the titanium aluminum nitride residue obtained in step (1) was mixed with 3000 g of sodium carbonate powder, 75 g of liquid alkali, 150 g of sodium chloride powder, and 37.5 g of manganese dioxide powder. After mixing and balling, the mixture was fed into an atmospheric roasting furnace. Nitrogen was introduced to remove air before roasting. The temperature was first raised to 300°C and maintained for 2 h. When the temperature was raised to 500°C, air was introduced. Finally, the temperature was raised to 900°C, and the holding time was 3 h. The furnace was maintained at atmospheric pressure, and a gas preheating device was installed at the front end of the furnace.

[0029] (3) Leaching: 2247 g of the roasted sand obtained in step (2) was ground to 500 mesh and added to 22470 mL of water for stirring and leaching. The pH value was monitored in real time during the process, and the pH value was maintained at not less than 14. If the pH value decreased, a small amount of sodium hydroxide powder was added to adjust it. The leaching temperature was 80°C, and the holding time was 2 h.

[0030] (4) Titanium extraction: The leaching slurry obtained in step (3) was filtered while hot. The filtering equipment was maintained at 100°C. 2020 g of sodium metatitanate filter cake (containing 606 g of water) was obtained by filtration. 6188 mL of water and 707 g of 98% sulfuric acid were added to prepare a sulfuric acid solution with a concentration of 1 mol / L. The mixture was stirred for 10 h. After acid washing, the filter cake was washed with water and roasted at 900°C for 1.5 h to obtain titanium dioxide.

[0031] (5) Aluminum extraction: Concentrated sulfuric acid was added to the filtrate obtained after acid washing in step (4), and the pH was adjusted to 7.5. After sufficient stirring, the filter cake was obtained by filtration. The filter cake was washed with water and naturally dried to obtain aluminum hydroxide.

[0032] (6) Manganese extraction: Concentrated sulfuric acid was added to the filtrate obtained after filtration in step (5), and the pH was adjusted to 1.5. After sufficient stirring, the filter cake was obtained by filtration. The filter cake was washed with water and dried to obtain manganese dioxide. The obtained manganese dioxide can be returned to step (2) for continuous use.

[0033] (7) Detection: The element extraction rate and product purity of each product were detected.

[0034] Example 3 A method for recycling PET-titanium aluminum nitride composite cutting debris, the specific steps are as follows: (1) Separation of PET: Take 2000g of cutting chips, freeze the cutting chips at-50℃ for 2h, and then send them to ball milling. Repeat the above-mentioned freezing and ball milling steps for 6 rounds. Then, add 2000g of the ball-milled material into 40L of water and stir until uniform. Ultrasonic treat for 5min, and mechanically stir for 3min. Repeat the above steps for 10 times, and then stand still. After extracting the surface liquid, filter the cake, which is the recovered PET material. Take the lower liquid and filter the cake, which is the titanium aluminum nitride residue. 2 After 5min of ultrasonic treatment and 3min of mechanical stirring, repeat the above steps for 10 times, and then stand still. After extracting the surface liquid, filter the cake, which is the recovered PET material. Take the lower liquid and filter the cake, which is the titanium aluminum nitride residue.

[0035] (2) Roasting: Take 1428g of the titanium aluminum nitride residue obtained in step (1), and mix it with 3000g of sodium carbonate powder, 50g of liquid alkali, 100g of sodium chloride powder, and 10g of manganese dioxide powder. After mixing and balling, send them to an atmospheric roasting furnace. Before roasting, first purge the air with nitrogen. First, heat to 320℃ and keep for 0.5h. Then, continue to heat to 500℃, and convert the gas to air. Finally, heat to 750℃ and keep for 4h. Keep the pressure in the furnace at normal pressure, and set a gas preheating device at the front end of the furnace.

[0036] (3) Leaching: Put 2415g of the roasted sand obtained in step (2) into a ball mill to refine to 100 mesh, and add 12075mL of water to leach by stirring. Monitor the pH value in real time during the process, and keep the pH value not lower than 14. If the pH value decreases, add a small amount of sodium hydroxide powder to adjust. The leaching temperature is 90℃, and the heat preservation time is 0.5h.

[0037] (4) Titanium extraction: Filter the leaching slurry obtained in step (3) while hot. The filter equipment needs to be kept at 100℃. Take the sodium metatitanate filter cake obtained by filtration (containing 808g of water), add 4821mL of water and 56.58g of 98% sulfuric acid to prepare a sulfuric acid solution with a concentration of 0.1mol / L. Stir thoroughly for 5h. After acid washing, filter the cake, wash it thoroughly with water, and roast it at 600℃ for 3h to obtain titanium dioxide.

[0038] (5) Aluminum extraction: In the filtrate obtained after acid washing in step (4), add concentrated sulfuric acid dropwise to adjust the pH to 7. After stirring thoroughly, filter the cake, which is aluminum hydroxide after being washed thoroughly with water and naturally dried.

[0039] (6) Manganese extraction: In the filtrate obtained after filtration in step (5), add concentrated sulfuric acid dropwise to adjust the pH to 2. After stirring thoroughly, filter the cake, which is manganese dioxide after being washed thoroughly with water and dried. The obtained manganese dioxide can be returned to step (2) for continuous use.

[0040] (7) Detection: The element extraction rate and product purity of each product.

[0041] The above merely provides the preferred embodiment of the present application, and is not used to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for recycling cutting debris from PET-titanium nitride aluminum composite materials, characterized in that, The specific steps are as follows: (1) Separation of PET: After the cutting chips are frozen at low temperature, they are ground evenly, and then cyclone separation and gravity flotation are performed to obtain PET powder and titanium aluminum nitride residue; (2) Calcination: The titanium aluminum nitride residue obtained in step (1) is mixed with sodium carbonate, liquid alkali, sodium chloride and manganese dioxide to form pellets and then calcined to obtain calcined sand; (3) Leaching: Grind the calcined sand obtained in step (2), add water and stir, then heat and leach; (4) Titanium extraction: After leaching, the sodium metatitanate filter cake is obtained by filtration. After acid washing, it is filtered to obtain filtrate I. The filter cake is washed with water and then calcined to obtain titanium dioxide. (5) Aluminum extraction: After adjusting the pH of the filtrate I obtained in step (4), stir and filter to obtain filtrate II. After washing the filter cake with water, aluminum hydroxide is obtained. (6) Manganese extraction: After adjusting the pH of the filtrate II obtained in step (5), stir and filter it. The resulting filter cake is washed with water and dried to obtain manganese dioxide.

2. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 1, characterized in that: In step (1), the low-temperature freezing temperature is -100℃ to -50℃, the time is 0.5-2h, and it is repeated 3-6 times; the liquid-solid ratio of the ground debris to water during gravity flotation is 20:1 mL / g.

3. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 2, characterized in that: In step (2), the liquid alkali is a sodium hydroxide solution with a mass percentage of 30%, and the mass ratio of the titanium aluminum nitride residue to sodium carbonate, liquid alkali, sodium chloride and manganese dioxide is 1:(3-5):(0.05-0.1):(0.1-0.2):(0.01-0.05).

4. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 3, characterized in that: In step (2), the roasting is carried out in a roasting furnace under a nitrogen atmosphere. The temperature is first raised to 300-320℃ and held for 0.5-2 hours. The temperature is then raised to 500℃ and switched to an air atmosphere. The temperature is then raised to 750-1000℃ and held for 1-4 hours. The roasting furnace is kept at normal pressure and an air inlet preheating device is installed at the front end of the furnace.

5. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 4, characterized in that: In step (3), the liquid-solid ratio of water to calcined sand is 5-10:1 mL / g, the pH is kept not lower than 14 during stirring, the heating temperature is 80-100℃, and the temperature is maintained for 0.5-2h.

6. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 5, characterized in that: In step (4), the pickling solution is a sulfuric acid solution with a final concentration of 0.1-1 mol / L. The liquid-solid ratio of the sulfuric acid solution to the sodium titanate filter cake is 3-5:1 mL / g, and the pickling time is 5-10h.

7. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 6, characterized in that: The roasting temperature in step (4) is 600-1000℃ and the time is 1-3h.

8. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 7, characterized in that: In step (5), the pH is adjusted to 7-8.

9. The method for recycling cutting debris from PET-titanium nitride aluminum composite materials according to claim 8, characterized in that: In step (6), the pH is adjusted to 1-2.

Citation Information

Patent Citations

  • Process for recovery of titanium values from complex matrix comprising titanium nitride

    CN1069072A